Fiscal capacity of German federal states: East-West gap narrows, but rich-poor divide grows - Kristina van Deuverden (DIW Weekly Report, 2025)
Even now, 35 years after German unification, the economic power and fiscal capacity of the eastern German federal states remain below average. In Germany's system of fiscal federalism, this leads to substantial financial transfers, a fact that repeatedly triggers political debate. Thereby, the low tax revenue of the economically weak states is also a consequence of the tax system-and by no means a problem that is confined to the east. While East German states have closed much of the gap with weaker western states, jointly these represent a stark contrast with the wealthiest states. If current trends continue-particularly the regionally uneven demographic developments-this division is likely to harden, meaning that compensation payments from the more affluent states will keep rising. This may well prompt these states to push for another reduction in their equalization transfers, which, just as in the previous financial reform, would allow them to evade part of their responsibility. Such an outcome should be avoided, not least because it was primarily the financially strong states that benefitted from the population losses in the eastern German states after unification.
Keywords: H77; 330; Fiscal federalism; tax revenue; public finance; Eastern Germany; unification